七種競技者のトレーニングとコンディションの関係: Session RPEと心拍変動に着目して - 木越, 清信; 鍋倉, 賢治; 伊藤, 明子 (コーチング学研究, 2023)
The main purpose of conditioning in athletes is to show the results of practice in a competition perfectly. The purpose of this study was to explore the possibility of training load quantifying by Session RPE and to evaluate the condition using heart rate variability (HRV) in a heptathlete. In this study, HRV, Hooper's score, and training load were monitored for 10 weeks to search the relationship between training and conditioning in a heptathlete. The subject of this study was a female elite Japanese heptathlete. As a result, a significant positive correlation was found between Monotony and Ln rMSSD (r＝0.781, p＜0.01). And a significant negative correlation was found between Monotony and Ln rMSSDcv (r＝－0.706, p＜0.01). In addition, the subjects developed appendicitis after the decrease of Ln rMSSD. Ln rMSSD is the HRV index which decreases due to decreased parasympathetic activity. There are various causes of appendicitis, and One of the causes of appendicitis is invasion by bacteria and viruses and immunological deterioration. In conclusion, it was suggested that Session RPE and HRV are the valid way to the evaluation of training load and condition in heptathletes objectively.